Executive charisma six steps to mastering the art of leadership - Benton, D. A. (McGraw Hill-Ascent Audio, 2022)
A proven six-step process for acquiring the style, flair, and credibility needed to make it to the top According to a recent Wall Street Journal article, managers who do not exude an all encompassing self-confidence, style, poise, and energy, in short, "executive presence", are highly unlikely to make it to the corner office. Unfortunately, the vast majority of managers, even the most talented and ambitious ones, are not born with these personal qualities. In this breakthrough book, bestselling author and world-renowned executive development coach D. A. Benton helps listeners acquire executive charisma. In Executive Charisma, Benton outlines a proven six-step approach for learning how to think, act, and relate to others like an executive. She provides powerful tools for fine-tuning the complete executive charisma skill set, including: interpersonal communications; managing upwards; confidence-building; business humor; executive-bearing; and more. Drawing upon her experience coaching clients at American Express, Century 21, Merrill Lynch, Nabisco, Viacom, Pepsi, and other top companies worldwide, Benton clearly defines executive charisma and explains why projecting a commanding professional demeanor is so fundamental to corporate success.